Digi Marketing Training for SMEs in Tangerang in increasing Sales - Sutikno Sutikno; Mery Ramadani; Melyanti Melyanti (Community Service Akseprin Journal, 2023)
The rapid development of social media can be used to expand the MSME market. However, not all MSME players know the opportunity to use social media for marketing. Through training and digitalization of MSMEs organized by service activity groups, it can help the community, especially MSME players, to market products through social media. With this work program, it is hoped that marketing can increase its own attractiveness and be able to expand marketing reach. In addition, useful in selling MSME products, the introduction of social media also aims to sharpen people's knowledge about using social media wisely. The results of the work program include increasing knowledge about the use of social media in marketing, as well as how to apply it to MSME actors. In addition, this activity is able to educate MSME players about the advantages and disadvantages of online marketing